2009
DOI: 10.1002/bem.20511
|View full text |Cite
|
Sign up to set email alerts
|

Large gradient high magnetic field affects the association of MACF1 with actin and microtubule cytoskeleton

Abstract: The intense inhomogeneous magnetic fields acting on the diamagnetic materials naturally present in cells can generate strong magnetic forces. We have developed a superconducting magnet platform with large gradient high magnetic field (LG-HMF), which can produce three magnetic force fields of -1360, 0, and 1312 T(2)/m, and three corresponding apparent gravity levels, namely 0, 1, and 2-g for diamagnetic materials. In this study, the effects of different magnetic force fields on osteoblast-like cells (MG-63 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…cDNA microarray reveals cytoskeleton-related genes sensitive to HMGE association of MACF1 with actin and microtubule cytoskeleton [32]. Tropomodulin 3 is a ubiquitous TMOD isoform present in non-erythroid cells, where it regulates dynamic actin processes [33].…”
Section: Discussionmentioning
confidence: 99%
“…cDNA microarray reveals cytoskeleton-related genes sensitive to HMGE association of MACF1 with actin and microtubule cytoskeleton [32]. Tropomodulin 3 is a ubiquitous TMOD isoform present in non-erythroid cells, where it regulates dynamic actin processes [33].…”
Section: Discussionmentioning
confidence: 99%
“…That is, the HMGE is a compound environment of magnetic field and gravity and it provides three apparent gravity levels as mg (weightlessness, 12 T), 1g (16 T), and 2g (hypergravity, 12 T) stably and continually for diamagnetic materials. Qian et al [21][22][23] have performed some studies about bone cells using this system and prove that it can be used to simulate weightlessness. Although this system is a complex environment, the effects induced by this environment can be analyzed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Although the increase of cell apoptosis is one of the significant consequences in cell structure and function that occurs in microgravity [31,32], such a high apoptotic rate resulted from simulated weightlessness at such a short time (for 12 h) has not been reported previously. Qian et al [17][18][19][20][21] demonstrated that the proliferation of MC3T3-E1 (inhibited) and MG-63 (accelerated) osteoblasts lines were affected by HMGE and the cell shape became more flat under mg condition. However, the apoptosis was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, osteoblasts resist the disrupted cytoskeleton to a certain extent. MACF1 is widely distributed across the osteoblasts and co-localized with cytoskeleton (Becker and Souza 2013), but the colocalization is remarkably reduced under DL with accumulation at perinuclear region (Qian et al 2009b), suggesting that MACF1 may function in graviperception. Connexin 43 (Cx43) forms gap junctions and hemichannels in bone cells directing cell-cell communication, which plays pivotal roles in bone development and remodeling (Plotkin and Bellido 2013).…”
Section: Mechanotransduction Of Bone and Immune Cells Under Microgravitymentioning
confidence: 97%